Effectiveness of Animated Video-Based Oral Health Education on Toothbrushing Skills among Preschool Children - Surayah Surayah; Pahrur Razi (Poltekkes Kemenkes Palu, 2026)
Background: Poor oral hygiene in preschool children remains a common public health problem and may lead to dental caries, gingivitis, pain, and impaired quality of life. Inadequate toothbrushing skills are an important contributing factor. Educational media such as animated videos may help children learn correct brushing techniques in an engaging way. This study aimed to evaluate the effect of animated video-based oral health education on toothbrushing skills among preschool children. Methods: This study used a pre-experimental one-group pretest-posttest design conducted at TK Khalifah Jambi, Jambi City, Indonesia, from January to March 2025. A total of 50 preschool children aged 4–6 years were selected using purposive sampling. Participants received a seven-minute animated oral health education video followed by demonstration and supervised toothbrushing practice. Toothbrushing skills were assessed using a structured observational checklist before the intervention and seven days afterward. Data were analyzed using the Wilcoxon signed-rank test with a significance level of p < 0.05. Results: The mean pretest toothbrushing skill score was 52.3 ± 10.6, which increased to 82.7 ± 8.4 at posttest. There was a statistically significant improvement in toothbrushing skill scores after the intervention (p < 0.001). Improvements were observed in brushing sequence, brushing duration, tongue cleaning, and rinsing practices. Conclusion: Animated video-based oral health education combined with demonstration and supervised practice was associated with improved toothbrushing skills among preschool children. This approach may be considered as a practical strategy for early childhood oral health promotion programs.